$\newenvironment {prompt}{}{} \newcommand {\ungraded }[0]{} \newcommand {\HyperFirstAtBeginDocument }[0]{\AtBeginDocument }$
1 : Consider the following functions: $f(x) = \sage {p1func1}$ and $g(x) = \sage {p1func2}$. Compute:

$f(g(x)) = \answer {\sage {p1ans1}}$

$g(f(x)) = \answer {\sage {p1ans2}}$

$(f\circ g)(x) = \answer {\sage {p1ans1}}$

$((g\circ f)(x) = \answer {\sage {p1ans2}}$

2 : Consider the following functions: $f(x) = \sage {p2func1}$ and $g(x) = \sage {p2func2}$. Compute:

$f(g(x)) = \answer {\sage {p2ans1}}$

$g(f(x)) = \answer {\sage {p2ans2}}$

$(f\circ g)(x) = \answer {\sage {p2ans1}}$

$((g\circ f)(x) = \answer {\sage {p2ans2}}$

3 : Consider the following functions: $f(x) = \sage {p3func1}$ and $g(x) = \sage {p3func2}$. Compute:

$f(g(x)) = \answer {\sage {p3ans1}}$

$g(f(x)) = \answer {\sage {p3ans2}}$

$(f\circ g)(x) = \answer {\sage {p3ans1}}$

$((g\circ f)(x) = \answer {\sage {p3ans2}}$

4 : Consider the following functions: $f(x) = \sage {p4func1}$ and $g(x) = \sage {p4func2}$. Compute:

$f(g(x)) = \answer {\sage {p4ans1}}$

$g(f(x)) = \answer {\sage {p4ans2}}$

$(f\circ g)(x) = \answer {\sage {p4ans1}}$

$((g\circ f)(x) = \answer {\sage {p4ans2}}$